PENGARUH TINGKAT KEMATANGAN BEBERAPA JENIS PISANG TERHADAP KADAR DEKSTRIN, NILAI GIZI DAN ORGANOLEPTIK TEPUNG PISANG - Abe, Wa; Wahyuni, Sri; Muzuni, Muzuni (Jurnal Sains dan Teknologi Pangan, 2017)
ABSTRACT The purpose of this study was to determine the effect of banana maturity level on organoleptic test, to determine theproximate content (water, ash, fat, crude fiber, protein and glucose contents), and tp determine the dextrin content onbanana flour. This study used Completely Randomized Design in a factorial pattern to assess organoleptic quality criteria ofbanana flour including color, flavor, taste, and texture. The results showed that organoleptic assessment of color, flavor,taste and texture of the preferred banana flour was found in T3 sample (Rather ripe Kepok banana’s flour), T4 sample(Unripe kepok banana’s flour), T2 sample (Unripe Raja banana’s flour) and (T3 and T4 samples). The banana flour producedin T2, T3 and T4 samples had moisture content of 8.91%, 6.96% and 7.35%, ash content of 0.30%, 0.67%, and 0.41%, fatcontent of 0.37%, 0.51% and 0.38%, fiber content of  0.20% , 0.13% and 0.15%, protein content of 0.53%, 0.38% and 0.18%and starch content of 0.53%, 0.22% and 0.37%. The dextrin contents of T2, T3 and T4 sample were 73.06%, 84.99% and63.77%. In general, the results of this study showed that banana flour favored and meet SNI standards of banana flour.Keywords: Banana flour, nutritional value, dextrin levels.  ABSTRAK  Tujuan penelitian ini untuk menentukan pengaruh tingkat kematangan pisang terhadap penilian organoleptik pada produktepung pisang yang disukai, penentuan kadar proksimat (kadar air, kadar abu, kadar lemak, kadar serat kasar, kadar proteindan kadar glukosa), dan penentuan  kadar dekstrin pada tepung pisang. Penelitian ini menggunakan Rancangan AcakLengkap dalam  pola faktorial untuk menilai kriteria penilaian organoleptik mutu tepung pisang  meliputi warna, aroma, rasa,dan tekstur. Hasil penelitian menunjukkan bahwa penilaian organoleptik warna, aroma, rasa dan tekstur  pada  tepungpisang  yang disukai panelis terdapat pada perlakuan T3 (tepung pisang kepok mengkal), T4 (tepung pisang kepok mentah),T2 (tepung pisang raja mentah) dan (T3 dan T4). Tepung pisang  yang dihasilkan pada perlakuan T2, T3 dan T4mengandung kadar air sebesar 8.91%, 6.96% dan 7.35%,  kadar abu  0.30%, 0.67%, dan 0.41%,  kadar lemak 0.37%,0.51% dan 0.38%, kadar serat 0.20%, 0.13% dan 0.15%,  kadar protein 0.53%, 0.38% dan 0.18% dan kadar pati sebesar0.53%, 0.22% dan 0.37%. Kadar dekstrin tepung pisang sample T2, T3 dan T4 yaitu 73.06%, 84.99% dan 63.77%. Secaraumum hasil penelitian ini menunjukkan  tepung pisang disukai dan memenuhi standar SNI tepung pisang. Kata kunci : Tepung pisang, nilai gizi, kadar dekstrin.